Scorpion bites in the north-western of Khuzestan province from May 2002 to December 2003 - Ghaderi H; Shariati Z; Ghodoosi A; Ziyaee M (Tehran University of Medical Sciences, 2006)
Background & Aim: Scorpion bites are one of the major health problems in some parts of Iran. This study has been conducted to evaluate the scorpion biting in north-western of Khuzestan province from May 2002 to December 2003. Methods & Materials: This study was a prospective case series conducted from May 2002 to December 2003. Location of the study was the Northwest region of Khuzestan Province. Results: From all 139 cases of scorpion bites by Androctonus crassicauda came to the clinic most bites were occurred during summer. All patients were treated conservatively without injecting anti-scorpion serum and discharged without any complication. Conclusion: The major threat in that region is because of Androctonus crassicauda bites. Considering that there is no need to inject anti-scorpion serum for these kinds of bites, further evaluation and doing more through studies about treatment is recommended. Moreover, no relation was seen between scorpion bites and different nights of month.